The relationship between feed efficiency, growth and group dominance dynamics in turbot (Scophthalmus maximus) - Luis Gomez-Raya; Wendy M. Rauw; Santiago Cabaleiro; Rubén Caamaño; L. Alberto Garcia-Cortes; Antti Kause (Spanish Journal of Agricultural Research, 2018)
Variation among families of turbot (Scophthalmus maximus) in growth, feed efficiency, and body weight variation was investigated. A total of 672 turbot (Scophthalmus maximus) originating from eight families (84 full-sibs per family) were used in this experiment. Body weight (BW) was recorded individually four times between approximately 250 and 370 days of age. Feed intake was measured for each tank during the three corresponding time periods. Feed efficiency was estimated for each tank based on the calculations of residual feed intake (RFI) and feed conversion ratio (FCR). The within-tank coefficient of variation in body weight (CV-BW) and residual body weight variation (RBWV) were calculated to evaluate group dominance dynamics. Components of variation attributable to families were estimated from linear and quadratic random regression orthogonal polynomials. The random quadratic family component explained 14% (RFI), 22% (FCR), 76% (BW), 50% (CV-BW), and 45% (RBWV) of the total variance. The family components were significant for BW, CV-BW and RBWV (p<0.001), and was very close to significance for FCR (p=0.052). The correlation between the intercept (grand mean) of RFI and FCR was highly significant (r=0.94). Intercepts of RFI and FCR were positively correlated with CV-BW and RBWV (r=0.09 to 0.12), however, the correlations were not significant. The results indicate differences between families in FCR, which may be used in selection programs aimed at improving feed efficiency.